Avaliação da mortalidade após o tranplante renal - Ruiz, Priscila Ruppel [UNIFESP] (2016)
Methods: This was a retrospective, single-center, case-control study which assessed 324 primary recipients of kidney transplant to evaluate the incidence of infection related deaths in the first 5 years after kidney transplantation. Case group (N = 162) consisted of patients who received renal transplantation in Hospital do Rim between Jan/2007 to Dec/2009 and died in the first five years after transplantation, excluding multi-organ transplant recipients , re-transplants and pediatric transplants. Control group (N = 162) was matched considering the date of transplantation; recipient age (+/- 5 years); donor age (+/- 5 years); recipient gender; donor gender; recipient race; induction with thymoglobulin and type of donor (living or deceased). Results: Patients in case group (death in 5 years) showed higher time on dialysis (53.9 ± 41.5 x 36.9 ± 31.0 months, p <0.001), higher incidence of pre-transplant diabetes (29% vs. 18.5% p = 0.026), lower level of education (5.6% x 13.6% of university graduates, p = 0.008), higher incidence of unemployment (48.8% vs. 32.7%, p <0.001), lower intermediate profession classification (4.9% vs. 17.9%, p <0.001), higher incidence of delayed graft function (41.3% vs. 29%, p = 0.012) lower serum creatinine and creatinine clearance MDRD , higher incidence of acute rejection, higher density of visits to the center (1.48 ± 1.32 x 0.76 ± 0.41 visits / month, p <0.001) and higher density of hospitalized days (12.69 ± 32, 71 x ± 2.78 16.26 days / month, p <0.001). Multivariate analysis identified as variables that impact on the risk of death: time on dialysis, intermediate profession classification, density of visits to the center, density of hospitalized days and peritoneal dialysis. Conclusion: Patients who died are patients with more pre-transplant comorbidities, worse post-transplant follow-up, with higher incidence of delayed graft function and acute rejection and worse renal function, and therefore required more outpatient visits and readmissions.